An evaluation of comparative treatment effects with high and low dose fluticasone propionate/formoterol combination in asthma. (December 2015) - Dissanayake, Sanjeeva; Jain, Meena; Grothe, Birgit; McIver, Tammy; Papi, Alberto
Abstract: Background: Despite extensive use of inhaled corticosteroid/long-acting β2 -agonist combinations in asthma, limited data evaluating dose–response for this combination class are available. The benefits of dose escalation and nature of patient subgroups likely to benefit are thus ill-defined. Method: In this randomised, double-blind, 8-week study the effects of two dose levels (100/10 and 500/20 μg b.i.d.) of a fixed combination of fluticasone/formoterol ( flutiform ® ) were compared in 309 patients. Treatment effects upon spirometric and symptom-based endpoints were examined in the overall population and in two subgroups defined a priori by % predicted FEV1 at baseline (≥40–≤60% ["severe" airways obstruction] and >60–≤80% ["moderate" airways obstruction]). Results: No dose–response was evident for spirometric outcomes (FEV1, FEV1 AUC0–12, PEFR) either overall or in either subgroup. At variance with the spirometric data, statistically significant dose-dependent differences were seen for nocturnal outcomes and consistent numerical differences were found across multiple symptom-based outcomes (symptom scores, sleep scores, rescue medication use, asthma control days, AQLQ scores, exacerbations); greater effects were noted with the higher dose of fluticasone/formoterol. Between-group differences for the overall population were driven by treatment effect differences in the "severe" subgroup. Conclusion: In this exploratory comparison a high dose of fluticasone/formoterol in asthmatic patients appears to provide additional improvement in symptom-based rather than spirometric outcomes. Additional benefits from high versus low dose treatment are most likely in patients with severe airway obstruction, although the doses at which ceiling effects are attained may vary between individuals. Trial registration: ClinicalTrials.gov identifier:NCT00734318 ; EudraCT number: 2007-001633-34.